UPAYA EDUKASI PENINGKATAN KUALITAS GENERASI SADAR KESEHATAN REPRODUKSI PADA REMAJA - Andi Sulastri; Sunarti, Andi Basniati, Mutmainnah Kamaruddin (JOURNAL OF COMMUNITY DEDICATION, 2023)
Adolescent age ranges from 10-24 years, which is a transitional phase from childhood to adulthood and is normal in human life. Population census data for 2020 shows that the number of teenagers aged 10–24 years is 67 million or 24% of the total population of Indonesia. Where healthy teenagers will become healthy adults and have healthy offspring with a quality life, so that teenagers become an important focus of attention in national development. The aim of this activity is for participants to understand adolescent reproductive health. The methods used were lectures, distribution of pamphlets and discussions, located at SMPN 15 Makassar in November 2023 and attended by 20 young men and women. This community service is carried out with counseling about adolescent reproductive health, followed by questions and answers and educational games as well as pre-tests and post-tests about reproductive health. The results of this counseling showed an increase in understanding of adolescent reproductive health, where the pretest was 30% and the posttest was 85%. Increasing teenagers' understanding of reproductive health will improve the quality of the generation that is aware of reproductive health.